Penguatan layanan perpustakaan perguruan tinggi vokasi melalui pengelolaan koleksi dan produksi konten digital - Muhamad Rizaldy Waluya (Universitas Pendidikan Indonesia, 2026)
This article reports on a community service intervention to strengthen the STIA LAN Bandung Polytechnic Library's services through collection management, digital content production, and accreditation support. The partner library faced three specific problems: the accumulation of 127 uncataloged alumni-donated books, unverified inventory data for Final Project deposit collections, and a lack of digital content for institutional branding. A service-learning approach was implemented over 25 working days (November 2025-January 2026) through three stages: preparation, implementation, and evaluation, with achievements measured using indicators adapted from Kirkpatrick's Level 2 (learning) and Level 3 (behavior) models. The results showed that 127 books were recorded in the Master Book; 342 Final Project deposit collections were verified through stocktaking with 94.7percent accuracy; six digital content pieces were produced (generating 1,200+ social media impressions); and one accreditation support report was completed. The novelty of this study lies in the integrated model that combines conventional collection management with digital branding strengthening within a single service-learning framework for the vocational library context. This achievement can serve as a replicable model for strengthening student-centered library services in vocational colleges.